Sexing freshwater turtles: penile eversion in Phrynops tuberosus (Testudines: Chelidae) - João Rodrigues; Diego Soares; José Silva (Acta Herpetologica, 2014)
Here, we described a noninvasive method for sexing freshwater turtles by stimulating penile eversion. We immobilized the neck and limbs of animals using fingers and, after some seconds, turtles everted their penis. This method was tested in 33 male Phrynops tuberosus, and 28 everted the penis. The efficiency of the method was not dependent of animal size, which reinforces its applicability. Our method allows sexing turtles in the field, avoiding killing the animal or causing major injuries in order to assess the sex.